Pecuária leiteira sustentável : Revisão bibliográfica - Silva Junior, Paulo Mateus da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Qualquer atividade sustentável, relacionada à produção pecuária ou não, está ligada ao fato de satisfazer as necessidades atuais sem que haja comprometimento das necessidades da geração futura. Uma atividade leiteira sustentável é aquela que vai se manter eficiente hoje para atender as necessidades de filhos e netos. Sendo assim, o leite sustentável é um produto da cadeia produtiva leiteira que promove uma exploração economicamente mais viável, ecologicamente mais correta e socialmente mais justa. Dessa forma, práticas mais sustentáveis e amigáveis ao meio ambiente na produção de leite ganham cada vez mais importância na escolha dos consumidores pelos produtos consumidos.

In this review on the importance of sustainable milk production in the performance of dairy cows, information about various sources was used, including research institutions, specialized websites, national and international magazines, technical bulletins, technical circulars, articles published in national and international journals and books. Any sustainable activity, related to livestock production or not, is linked to the fact of satisfying current needs without compromising the needs of the future generation. A sustainable dairy activity is one that will remain efficient today to meet the needs of children and grandchildren. Thus, sustainable milk is a product of the dairy production chain that promotes a more economically viable, ecologically more correct and socially fairer exploitation. In this way, more sustainable and environmentally friendly practices in milk production gain more and more importance in the choice of consumers for the products consumed.
Sustainable dayri farming : Bibliographic Review
Keywords: Sustentabilidade; Agroecologia; Leite